Bali - O'Dwyer, Simon, 1969- (2002)
"A nation mourns the death of 288 people to a bomb in the city of Kuta, Indonesia or better known as Bali, a favourite holiday spot for Australian tourists. As Australia absorbed the impact by a terrorist organisation against its people flowers began to mount on the steps of Parliament House in Melbourne along with every other capital city in the country. Looking at the thousands of flowers from the ground I knew the picture needed to be taken from above the scene looking down. After making a phone call to the Speaker of the House I was granted permission to photograph from the roof. On a wet Melbourne day I tied mysef to a piece of rope and with the help a Parliamentary employee I was lowered over the ledge to photograph the scene. Afraid of falling from such a dangerous position I took three photographs before being pulled back to safety. The photograph appeared in The Age newspaper as an image of steps filled with thousands of flowers and a pathway between them in the shape of a cross. Photographed with a Canon 1D digital camera using a 17mm lens."--Simon O'Dwyer.
Part of collection: Simon O'Dwyer collection of photographs.
Title supplied by photographer.
Also available online
Published in: The Age.
Keywords: Victims of terrorism -- Monuments -- Victoria -- Melbourne -- Photographs; Mourning customs -- Victoria -- Melbourne -- Photographs; Wreaths -- Victoria -- Melbourne -- Photographs; Bali Bombings, Kuta, Bali, Indonesia, 2002 -- Public opinion -- Photographs